Bonding of facial silicon with nanoparticles to an acrylic resin substrate - Haddad, Marcela Filie [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Moreno, Amalia [UNESP]; Naves, Lucas Zago; Sonego, Mariana Vilela [UNESP] (Elsevier B.V., 2014)
The aim of this study was to evaluate the influence of different adhesive techniques and accelerated aging on the bonding of maxillofacial biomedical silicone to an acrylic resin substrate. 960 acrylic resin samples (PMMA) were manufactured and bonded to the silicone with or without oil painting and/or opacifier. Both materials were bonded through mechanical retentions and/or application of primers (DC 1205 primer and Sofreliner primer S) and adhesive (Silastic Medical Adhesive Type A) or not (control group). The samples dimension were 75-mm length, 10-mm width and 6-mm thickness.The samples were divided in 4 groups (n=240) for the pigmentation variable, and 12 subgroups (n=20) accordingly to the bonding technique. Half of the samples of each group underwent the peel test at baseline and the fracture pattern was measured through direct observation and SEM and then classified into adhesive, cohesive and both failure. The remaining samples were submitted to accelerated aging (8 hours ultraviolet light irradiance was at a temperature of 60 +/- 3 degrees C and 4 h - a dark condensation period was at a temperature of 45 +/- 3 degrees C) during 1008 hours and the peel test, direct observation and SEM were performed. The peel value needed to separate the resin from silicone (PS) was statistically analyzed with the ANOVA variance test and the Tukey test (p < 0.05). The failure pattern was assessed statistically through the qui square test and the fisher exact test. The bond strength test results indicated a statically significance (p < 0.05) for all factors. These values raised after the aging period, and the oil painting group presented the higher mean value (PS=3.53 N/mm). Groups with were applied the Sofreliner Primer presented higher bond strength values than other subgroups for both periods of evaluation. The factors time and technique influenced significantly in failure pattern, the most common failure was mixed failure (n=671=69.9%) and the least common was the cohesive one (n=109). Greater PS values were presented by the subgroups pigmented with oil painting, without scratches and that received the sofreliner primer after the accelerated aging period. The sofreliner primer promotes a higher adherence between acrylic resin and facial silicone and the incidence rate of both failure augmented after the aging period. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Acrylic resin; Silicone elastomer; Nanoparticles; Maxillofacial prostheses; Aging